THE EFFECT OF THERMAL RADIATION AND VARIABLE VISCOSITY PARAMETERS ON A FLUID FLOW DOWN ALONG AN INCLINED PLANE WITH FREE SURFACE - Usman M..A.; Onitilo S..A.; Moshood S..T, (Tikrit Journal of Engineering Sciences, 2020)
This paper investigates the effects of thermal radiation and variable viscosity flow down along an inclined plane with boundary conditions at free surface. The major problem includes internal heat generation, increase or decrease in temperature, and other thermophysical properties. The thermophysical properties include Grashof number, Nusselt number, Viscosity and Solar radiation parameter. The problems created have not been examined. Thus, this work examined the effect of temperature and velocity profiles on the various values of coefficient of viscosity, also the effects of solar radiation parameter on the major property of the fluid flow down along an inclined plane. The partial differential equations for the problem are continuity, momentum and energy equations. These are nonlinear dimensionless equations governing the fluid flow down the inclined plane using integration method. The equations for the fluid flow, temperature and velocity of the problem are reduced to their final forms using perturbation method. Analytical expressions are employed to obtain the value of the velocity and temperature profiles in terms of parameters under the considerations in the flow field. The parameters are the major factors influencing the properties of the fluid flow down along an inclined plane. Hence, the viscosity of the fluid increases as the velocity of the fluid decreases while increase in the solar radiation parameter increases velocity of the fluid. Also the quantities of radiant energy absorbed by the fluid flow bring changes in the temperature of the fluid. Increase in Nusselt decreases the velocity of the fluid. Grashof number increases while the temperature of the fluid decreases. In conclusion, viscosity of the fluid decreases with an increase in temperature due to cohesion and molecular momentum exchange between fluid layer and the parameters are found to have a significant effect over the velocity and temperature profiles of the fluid flow down an inclined plane at free surface. It will also useful for the 13 industries in the production of the various fluids (liquid or gas) such as vegetable oil, palm oil and steam generation along an inclined plane and so on.